Resistência de união ao cisalhamento na colagem de bráquetes ortodônticos metálicos a dentes artificiais de acrílico - Cumerlato, Marina Lúcia (2013)
Introduction : The aim of this study was to evaluate, in vitro, the effects of different surface treatments and aging on the shear bond strength of metal orthodontic brackets bonded to prefabricated resin denture teeth. Methods : One hundred and ninety two upper central incisors (Dentsply) were randomly divided into two groups according to whether or not the aging of the teeth. The aging occurred by immersion in distilled water and incubation teeth at 37°C during 90 days. Each group was randomly divided into four subgroups, according to the surface treatment rendered: no treatment (control), roughening with diamond bur, drilling with diamond bur and sandblasting with aluminum oxide 50μm. Brackets were bonded equally in all groups with Transbond XT (3M Unitek, Monrovia, CA, USA). After one week of storage in distilled water at 37°C, the specimens were taken to a universal testing machine (Emic DL 2000 ®) and subjected to shear load, in an occluso-gingival direction at a crosshead speed of 0.05 mm / min. The types of fractures were classified according to the Adhesive Remnant Index (ARI). Data were analyzed by ANOVA, Tukey and Kruskal-Wallis tests. Results : The surface treatment increased the bond strength, however, only sandblasting with aluminum oxide and drilling with drill promoted clinically acceptable values for orthodontic purposes (p<0,05). The aging of the teeth did not alter significantly the bond strength. There was a predominance of adhesive failures, i.e. between the tooth surface and the adhesive. Conclusions : bonding brackets to prefabricated resin denture teeth only resist to orthodontic and chewing forces if the surface of the teeth is sandblasted with aluminum oxide or drilled with a bur to create mechanical retention, independent of aging of the teeth.